2017
DOI: 10.2174/1570163814666170117120005
|View full text |Cite
|
Sign up to set email alerts
|

Pimping up Drugs Recovered, Superannuated and Under Exploited Drugs - An Introduction to the Basics of Drug Reprofiling

Abstract: Drug development has moved along way forward from the days of with doctors peddling cauldrons of herbs and spices, however, the process can still miss opportunities for full exploitation of a drug’s potential. Drug reprofiling provides a chance for an established or a forgotten drug to move into a new area of therapy, whether related to the known effects or in a completely new area. In an era of environmental awareness and spiraling costs for traditional drug development, a strategy to squeeze every benefit ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Some repurposed medicines require product changes (e.g., change in dose, pharmaceutical form, route of administration) or are combined with other medicines or medical devices in the new indication. This can be a commercially interesting repurposing strategy as product changes may generate new intellectual property and enable a pharmaceutical developer to rebrand a product for its new use (Novac, 2013;Dilly and Morris, 2017). A final scenario covers the repurposing of approved medicines that are out of basic patent or regulatory protection and are used "as-is," thus do not require any substantial product changes (Bloom, 2016).…”
Section: Box 1 | Repurposing a Medicinementioning
confidence: 99%
“…Some repurposed medicines require product changes (e.g., change in dose, pharmaceutical form, route of administration) or are combined with other medicines or medical devices in the new indication. This can be a commercially interesting repurposing strategy as product changes may generate new intellectual property and enable a pharmaceutical developer to rebrand a product for its new use (Novac, 2013;Dilly and Morris, 2017). A final scenario covers the repurposing of approved medicines that are out of basic patent or regulatory protection and are used "as-is," thus do not require any substantial product changes (Bloom, 2016).…”
Section: Box 1 | Repurposing a Medicinementioning
confidence: 99%
“…However, a report from June 2017 on pharmaceutical incentives and rewards in Europe showed that this last incentive had never been granted for any centrally approved substance (Copenhagen Economics, 2018). In certain cases, medicine developers may choose to reformulate, protect (e.g., through second medical use patents) and rebrand an established medicinal product to create sufficient legal and strategic protection from generic competitors (Smith, 2011;Novac, 2013;Dilly and Morris, 2017). For developers other than the original marketing authorization holder, a new full marketing authorization application may even offer a 10-year period of data and marketing protection for the repurposed product (Murteira et al, 2014a).…”
Section: Regulatory Incentives For Marketing Authorizationmentioning
confidence: 99%
“…Third, sometimes a new dosage form, route of administration, strength, xed combination or formulation of the existing medicine is needed for use in a new therapeutic indication. Such changes may generate new IP and can enable a pharmaceutical developer to rebrand a product for its new use, making it a commercially interesting repurposing opportunity (7)(8)(9). A fourth and nal scenario covers the repurposing of approved medicines that are out of basic patent or regulatory protection and that do not require any signi cant product changes, which is sometimes referred to as generic or off-patent drug repurposing (10).…”
Section: Introductionmentioning
confidence: 99%